Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2013
DOI: 10.1017/s1041610213000252
|View full text |Cite
|
Sign up to set email alerts
|

Establishing the motivations of patients with dementia and cognitive impairment and their carers in joining a dementia research register (DemReg)

Abstract: There are currently major projects within the United Kingdom to increase the number of patients on dementia registers and to further involvement in dementia research. This study, to the best of our knowledge, is the first to assess the motivations of patients and carers for joining a dementia research register in the United Kingdom, and the findings highlight the importance of altruistic motives.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
10
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 12 publications
4
10
0
Order By: Relevance
“…The current study showed that individuals were more likely to enroll in research studies when they believed that their participation would help improve the health of others and themselves, as well as learn about their health. These findings are congruent with those of prior studies examining the decision-making of both AD patients and caregivers, two of which found that the main reasons patients joined a dementia registry, were to help others (44% of patients) and themselves (29%) [ 21 ], [ 23 ]. Similar to previous work, individuals in the current study were less likely to enroll if participation would require significant amounts of time and traveling (i.e., traveling to the study site several times per week) [ 14 ], [ 34 ].…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…The current study showed that individuals were more likely to enroll in research studies when they believed that their participation would help improve the health of others and themselves, as well as learn about their health. These findings are congruent with those of prior studies examining the decision-making of both AD patients and caregivers, two of which found that the main reasons patients joined a dementia registry, were to help others (44% of patients) and themselves (29%) [ 21 ], [ 23 ]. Similar to previous work, individuals in the current study were less likely to enroll if participation would require significant amounts of time and traveling (i.e., traveling to the study site several times per week) [ 14 ], [ 34 ].…”
Section: Discussionsupporting
confidence: 89%
“…However, other barriers are related to an individual’s interest in a study and decision to enroll or decline participation. For example, fewer positive attitudes towards research and an aversion to drug-related side effects have been associated with disinterest in clinical trial participation [ 11 ], [ 13 ], [ 21 23 ]. In this study, we explored how interest in pharmaceutical trials compared with interest in clinical research studies with different characteristics, including studies using other types of interventions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cronbach's α was good for all four factor-based scores, as shown in the bottom row in table 1 . As in some other studies, 40 monetary reward was not rated to be very important and did not load uniquely on any factor. Time and effort for participation also did not load uniquely on a single factor, although the length of the study did load on the who and what factor.…”
Section: Resultsmentioning
confidence: 67%
“…For example, participation may yield positive psychological impact on self-confidence, self-worth and the perceived benefit that the volunteer provides societal value [41] and even free physical exam and testing. In addition, it has also been shown that altruism (aspirational benefit) – that is, potential benefit to their relatives, to future sufferers or to society – also may be a perceived benefit of entering a clinical trial [42]. …”
Section: The Ethical Challengesmentioning
confidence: 99%